Productivity Measurement with Natural Capital. (25th August 2016) - Brandt, Nicola; Schreyer, Paul; Zipperer, Vera
Abstract : This paper proposes a measurement framework that explicitly accounts for the role of natural capital in productivity measurement. It is applied to aggregate economy data from the OECD Productivity Database, with natural capital data from the World Bank. It is shown that the direction of the adjustment to productivity growth depends on the rate of change of natural capital extraction relative to the rate of change of other inputs. The extended framework also makes the contribution of natural capital to economic growth explicit. This can be useful for countries relying on non‐renewable resources to better understand the need to develop other sources of growth—human or productive capital—to prepare for times of scarcer resource endowments. The framework can readily be applied to more encompassing natural capital data, once it becomes available.